Epidural Anesthesia to Facilitate Organ Blood Flow During the First Penile Transplantation in the United States: A Case Report. Issue 9 (1st May 2018) - Ruscic, Katarina J.; Zamora-Berridi, Grettel J.; McGovern, Francis J.; Cetrulo, Curtis; Winograd, Jonathan M.; Eberlin, Kyle R.; Bojovic, Branko; Ko, Dicken S.; Anderson, T. Anthony
Abstract : Regional anesthesia has been used to help create local sympathectomy and improve blood flow in plastic surgery procedures involving tissue grafts and flaps. However, anesthetic techniques that reduce systemic vascular resistance must be used with caution in patients with aortic stenosis (AS). Combined neuraxial and general anesthesia with careful titration of the local anesthetic dose can be a safe approach for patients with AS undergoing microvascular procedures. We present the anesthetic management of the first North American penile transplant, on an obese patient with moderate AS.